ADVANCE COMPUTER ARCHITECTURE - Jatiwal, Monika; Arora, Chetna; Arora, Charu (IJRDO -Journal of Computer Science Engineering, 2015)
This paper presents novel methods in teaching advanced computer architecture courses. These methods include presenting fundamental computer architecture issues employing visual aids to teach fundamentals concepts like pipelining and processing. This paper studies about the history for Advance computer architecture. This paper explains about the parallel processing, architecture of parallel processing, pipelining and its role.